Power efficient CoMP‐joint transmission with two stage QoSs. Issue 4 (5th January 2016) - Kim, Seung‐Yeon; Cho, Choong‐Ho
Abstract: Power efficiency has become an important design goal for wireless communications, and a coordinated multi‐point (CoMP) with joint transmission (JT) scheme can be implemented to improve the cell edge throughput by increasing the signal‐to‐interference ratio, which in turn leads to power savings through cooperative transmission. To this end, we propose a power control scheme in which the cooperating base station can reduce its own transmission power while remaining within two stage quality of service (QoS) constraints, including the call‐blocking probability and outage probability. For the two QoS constraints, we introduce call admission control and signal‐to‐interference ratio models for CoMP‐JT that consider a two‐dimensional Markov chain and the sum of multiple exponential random components. The results of the call blocking and outage probabilities are used to obtain the power consumption model and analyse the performance for the CoMP‐JT with the proposed power control technique. Both the analytical and numerical results show that the proposed power control strategy can reduce the power consumption for the cellular network with the two stage QoSs. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Power efficiency has become an important design goal for wireless communications, and a coordinated multi‐point with joint transmission scheme can be implemented to improve the cell edge throughput by increasing the signal‐to‐interference ratio, which in turn leads to power savings through cooperative transmission. To this end, we propose a power control scheme in which the cooperating base station can reduce its own transmission power while remaining within two stage quality of service constraints, including the call‐blocking probability and outage probability. For the two quality of service constraints, we introduce call admission control and signal‐to‐interference ratio models for coordinated multi‐point with joint transmission that consider a two‐dimensional Markov chain and the sum of multiple exponential random components.